Surgery review - Cooper, Michol A.; Makary, Martin A. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"Surgery Review is a comprehensive review presented in a unique format. Topics are introduced with case presentations and relevant diagnostic and management information is then summarized in easy-to-remember capsules with exam pearls interjected throughout. All areas of general surgery are covered, including the subspecialty areas. There is also a section on basic science found on the in-training exam and written boards, and a section of anesthesia, trauma, and critical care. Unlike many other books, General Surgery Review excludes controversial management in order to present an easy-to-remember foundation of knowledge. Thus, the book focuses on "the basics" to provide the reader with a broad command of the field. This title is indispensable to residents studying for in-training exam or boards, and is also popular with practitioners preparing for their recertification exam in general surgery. New Features : Full color format. New emphasis on color diagrams to help explain concepts and procedures. Key Features : covers all areas taught in a general surgical residency easy to read and remember quick review unique format mixes a case approach and bulleted review format" -- Provided by publisher